Armazenamento de sementes de cana-de-açúcar para o melhoramento genético - Tanno, Wellington Quadros (Universidade Federal de São Carlos, 2020)
Sugarcane is an important crop for Brazil, whose production area extends over approximately 10 million hectares, making the country the world's largest producer. Sugarcane Breeding is responsible for the production and release of new cultivars, more adapted to production environments, as well as tolerant to the main causes of biotic and abiotic stress. The beginning of this process is based on the generation of genetic variability through sexual reproduction and seed production. Seed storage techniques are necessary to maintain their physiological quality throughout the period necessary for their use. The objective was to compare two conditions of storage of sugarcane seeds to maintain their physiological potential. For this purpose, 16 crosses were used whose seeds were stored under two conditions: cold chamber with temperature control (8ºC) and relative humidity (30%) and another in a refrigerated room (18ºC) without controlling the relative humidity of the air. The seeds were stored for a total period of eight months, and the evaluations were carried out every two months to determine the physiological potential of the seeds based on the germination tests (carried out on germitest paper) and emergence tests (carried out on substrate), in addition to monitoring the content of seed water. The results showed that the emergence test performed on substrate showed a higher rate of seedling formation than the germination test, however for both tests there were interactions between the different crosses, conditions and storage period. Generally, in the cold chamber condition the seeds remained viable throughout the stored period, and in the refrigerated room it was found that the seeds significantly reduced their viability after the fourth month of storage. It was also noted that the different crosses have variable germination and/or emergence rates. However those with the lowest rates have lost their viability with storage, so it is recommended that only the lots with the greatest physiological potential be stored.
Seed storage for sugarcane breeding
Keywords: Câmara fria; Germinação; Emergência; Cold room; Germination; Emergence; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA